Endoscopic dacryocystorhinostomy - Milojević Milanko; Avramović Siniša; Kostić Bratislav; Sotirović Jelena; Perić Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Intensive epiphora (lacrimal apparatus disease) can make difficult daily routine and cause ocular refraction disturbances. In most cases ethiology is unknown, rarely occurs after nose surgical procedures, face fractures, in Wegener granulomatosis, sarcoidosis and malignancies. The aim of this study was to evaluate efficacy of endonasal endoscopic surgical procedure with the conventional surgical instruments in treatment of nasolacrimal obstructions. Methods. This retrospective study included 12 female patients with endonasal endoscopic surgical procedure from Otorhinological and Ophtalmological Departments of Military Medical Academy, Belgrade from September 2007 to April 2009. Preoperative nasal endoscopy was performed in order to reveal concomitant pathological conditions and anatomic anomalies which could make surgical procedure impossible. Computerized tomography was performed only in suspect nose diseases. Surgical endonasal endoscopic procedure was performed by otorhinolaryngologist and ophtalmologist in all patients. The patients had regular controls from 2 to 20 months. Results. A total of 12 female patients, age 34-83 years, were included in our study. Epiphora was a dominant symptom in all patients. In two patients deviation of nasal septum was found, and in other one conha bulosa at the same side as chronic dacryocystitis. All patients were subjected to endonasal dacryocystorhinostomy (DCR) by endoscopic surgical technique using conventional instruments. Concomitantly with DCR septoplastics in two patients and lateral lamictetomy in one patient were performed. There were no complications intraoperatively as well as in the immediate postoperative course. In two patients the need for reoperation occurred. Conclusion. Endoscopic DCR is minimally invasive and efficacious procedure for nasolacrymal obstructions performed by otorhinolaryngologist and ophtalmologist. Postoperative recovery is very fast.